Characteristics of gastroesophageal reflux disease in our country - Zeynel MUNGAN; Kadir DEMİR; M. Derya ONUK; Vedal GÖRAL; Güngör BOZTAŞ; Fatih BEŞIŞIK; Bülent YILDIRIM; Oktay YEĞİNSU (Turkish Journal of Gastroenterology, 2019)
-